2017
DOI: 10.1016/j.tig.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Speech and Language: Translating the Genome

Abstract: Investigation of the biological basis of human speech and language is being transformed by developments in molecular technologies, including high-throughput genotyping and next-generation sequencing of whole genomes. These advances are shedding new light on the genetic architecture underlying language-related disorders (speech apraxia, specific language impairment, developmental dyslexia) as well as that contributing to variation in relevant skills in the general population. We discuss how state-of-the-art met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 126 publications
2
56
0
Order By: Relevance
“…Previous studies have suggested that language-related cognitive performance is highly heritable (e.g., (Dale et al, 1998;Guen, Amalric, Pinel, Pallier, & Frouin, 2018;Newbury, Bishop, & Monaco, 2005)), and that brain activations associated with semantic comprehension tasks are also heritable (Guen et al, 2018). Moreover, genetic factors also play a substantial role in susceptibility to languagerelated neurodevelopmental disorders such as childhood apraxia of speech (Eising et al, 2018), developmental language disorder (specific language impairment) and developmental dyslexia (Deriziotis & Fisher, 2017). Crucially, although a small number of genessuch as FOXP2 (e.g., (Fisher & Scharff, 2009;Lai, Fisher, Hurst, Vargha-Khadem, & Monaco, 2001))have now been unambiguously linked to language-related disorders, these genes cannot by themselves explain the large majority of heritable variation, nor can they conceivably create or maintain the necessary brain circuits underlying language without interacting with a large number of other genes (Graham & Fisher, 2015;Konopka & Roberts, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that language-related cognitive performance is highly heritable (e.g., (Dale et al, 1998;Guen, Amalric, Pinel, Pallier, & Frouin, 2018;Newbury, Bishop, & Monaco, 2005)), and that brain activations associated with semantic comprehension tasks are also heritable (Guen et al, 2018). Moreover, genetic factors also play a substantial role in susceptibility to languagerelated neurodevelopmental disorders such as childhood apraxia of speech (Eising et al, 2018), developmental language disorder (specific language impairment) and developmental dyslexia (Deriziotis & Fisher, 2017). Crucially, although a small number of genessuch as FOXP2 (e.g., (Fisher & Scharff, 2009;Lai, Fisher, Hurst, Vargha-Khadem, & Monaco, 2001))have now been unambiguously linked to language-related disorders, these genes cannot by themselves explain the large majority of heritable variation, nor can they conceivably create or maintain the necessary brain circuits underlying language without interacting with a large number of other genes (Graham & Fisher, 2015;Konopka & Roberts, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, replication of our findings in future genetic association studies of brain structure in sufficiently large family-based populations that are less susceptible to impacts of population stratification 54,55 would allow further verification of the results presented here. Finally, future studies focusing on understanding genetic influences on behavioral and cognitive traits (language, motor skills) 56 combined with GWAS of their neurobiological substrates (like this one) may provide a more complete picture of how shifts in genetic variation across time might yield changes in brain structure and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…But despite the rarity of imprinting in the genome, there is evidence that some imprinted genes affect linguistic and communicative behavior . While none of the genes that have been robustly implicated in language‐related disorders, e.g., FOXP2 and CNTNAP2 , are known to be imprinted (see the Supporting Information for a full list), there is evidence that others may be. One reason is the parent‐of‐origin effects identified in a number of genomic regions associated with language phenotypes, including significant paternal effects at 14q12, suggestive maternal effects at 5p13, and possible parent‐of‐origin effects in a chromosomal deletion in the 15q13.1–13.3 region, which might underlie different clinical manifestations for the same chromosomal rearrangement .…”
Section: Inferring Selfishness Versus Altruism From Imprinted Genesmentioning
confidence: 99%